Aloe-Gel Coating for Delaying Physicochemical Change of Fresh-Cut Mango - Luh Suriati; I Putu Candra; I Komang Supardika (SEAS (Sustainable Environment Agricultural Science), 2021)
Fresh-cut arumanis mango is current popular product, stimulated by lifestyle and community needs for quality fruit with little preparation. Stripping and cutting spur the damage of fresh-cut mangoes faster than whole mangoes. Aloe vera gel coating as an alternative to maintain the characteristics of fresh-cut mangoes and extend shelf life. This study aims to delaying the physicochemical change of fresh-cut mango with aloe vera edible coating. The design used is a completely randomized design (CDR) of two factors, namely the ratio of dilution of aloe vera gel with aquadest 1:0, 1:1 and 1:2. Factor II, duration of immersion 1, 2 and 3 minutes with observations on the 5th and 10th days stored at cold temperatures (7± 1) °C. Observation variables include physical properties, namely weight loss, color and texture. Whereas observations of chemical properties, namely pH, total solubvle solid, water content and vitamin C. The best results were obtained in a combination of 1:1 aloe vera gel with 3 minutes immersion with a weight loss value of 1.40%, color b (∆E) 63.12, texture 6.82N, pH 4.65, TSS 24.60°Brix, moisture content 83.51% and vitamin C 35.60mg/100g).